2021
DOI: 10.1021/acs.analchem.0c04155
|View full text |Cite
|
Sign up to set email alerts
|

Novel Method Based on Hollow Laser Trapping-LIBS-Machine Learning for Simultaneous Quantitative Analysis of Multiple Metal Elements in a Single Microsized Particle in Air

Abstract: Elemental identification of individual microsized aerosol particles is an important topic in air pollution studies. However, simultaneous and quantitative analysis of multiple constituents in a single aerosol particle with the noncontact in situ manner is still a challenging task. In this work, we explore the laser trapping-LIBS-machine learning to analyze four elements (Zn, Ni, Cu, and Cr) absorbed in a single micro-carbon black particle in air. By employing a hollow laser beam for trapping, the particle can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Compared to the three metal elements, the prediction performance of the VIP-RF calibration model for the Zn element is the best, which has the best correlation and the lowest values of MREP and RMSEP. After the smoothing spectral pretreatment and various variable selection methods, the performance of RF models is improved compared with our previous work …”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Compared to the three metal elements, the prediction performance of the VIP-RF calibration model for the Zn element is the best, which has the best correlation and the lowest values of MREP and RMSEP. After the smoothing spectral pretreatment and various variable selection methods, the performance of RF models is improved compared with our previous work …”
Section: Resultsmentioning
confidence: 96%
“…Chen et al combined standard normal variation (SNV) spectral preprocessing and feature variable extraction methods to establish an RF calibration model based on the mid-infrared (MIR) spectra and LIBS spectra for qualitative analysis of soil pH . In our previous research, we investigated the laser trapping–LIBS combined with RF to quantitatively analyze four metal elements in a single particle . However, being a single particle, in the process of LIBS signal acquisition, the size of the single particle and other factors will cause instability of the spectral signal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, Niu et al proposed an optical trapping approach based on the use of a hollow cw laser beam, and successfully demonstrated that OT-LIBS can be applied for the quantitative determination of metal concentrations in individual, 2 mm black carbon aerosol particles. 256 In other studies, nL volume droplets and 1-3 micrometer aerosol particles were also successfully trapped and individually analyzed by LIBS. Järvinen et al 257 used an electrodynamic, whereas Meneses-Nava et al 258 an acoustic levitator for the trapping of particles.…”
Section: Methodology and Applicationsmentioning
confidence: 99%
“…Laser trapping-LIBS and machine learning was investigated by Niu et al 115 for the determination of 4 elements absorbed in a single micro-carbon black particle in air. The authors employed a hollow laser beam for trapping, which was proposed as a possible method for online single aerosol particle analysis.…”
Section: Laser Induced Breakdown Spectroscopy (Libs)mentioning
confidence: 99%